Analisa Karakteristik Mutu Sabun Padat Ekstrak Kulit Buah Manggis (Garcinia Mangostana L.) Berbahan Dasar Minyak Jelantah - Mita Susanti, Maria; Toni Juliantoro, Benediktus (Jurnal Farmasi (Journal of Pharmacy), 2021)
The use of used cooking oil can cause various diseases when consumed and will even cause environmental pollution if disposed of without processing. Therefore, efforts need to be made to utilize used cooking oil into products that can increase economic value, one of which is oil-based products such as solid soap. A good soap is not only able to clean the skin from dirt, but also contains substances that can counteract the effects of free radicals such as antioxidants. Mangosteen rind (Garcinia mangostana L.) is a source of natural antioxidants containing xanthones with an IC50 of 2.710 ppm. This study aims to make and analyze the quality characteristics of solid soap mangosteen rind extract based on used cooking oil. This study analyzed the quality characteristics of solid soap preparations including organoleptic tests, pH, free fatty acid levels, foam stability, water content and free alkali levels. Data analysis was done descriptively. The results showed that the quality characteristics of solid soap were in accordance with the quality requirements, namely organoleptic solid form, pH 10, foam stability 89.33%, moisture content 14.33%, free fatty acid content 1.54% and free alkali content 0.07%.